Perkecambahan Dan Pertumbuhan Benih Pala(Myristica fragrans Houtt) Akibat Lama Perendaman Pada Atonik Dan Komposisi Media Tanam - Tony Tony; Bahrudin Bahrudin; Iskandar Lapanjang (Universitas Tadulako, 2015)
This research aimed at determining the process of germination and growth of nutmeg seeds to obtain superior nutmeg seeds in Baolan Sub District of Tolitoli District. The research was conducted in two stages of experiments. The first stage involved soaking the seeds under different periods including with no soaking (A0), two hour soaking period (A1) and three hour soaking period (A2). This experiment used a Completely Randomized Design where each treatment had seven replicates. Greatest germination rate of 34.29% was found in the three hour soaking period after the seeds were allowed to sproud for six weeks. This was significantly different from the other two treatments under which treatments the germination rate was only 26.43%. At the second stage, the soaking period treatments were combined with various growing media including T1 (soil:sand:cow manure bokashi; v/v/v), T2 (soil:sand:cow manure bokashi; v/v/2v), and T3 (soil:sand:cow manure bokashi; v/v/3v) . The experiment was arranged in a Two Factorial Randomized Block Design where each treatments had four replicates. The average seedling height of 18.85 cm found in the A2T3 treatment 12 weeks after planting (WAP) was significantly higher than in the A1T2 and A0T1 under which treatments the heights were only 14.45 cm and 12.77 cm, respectively.